Translation and psychometric evaluation of Self-Care of Hypertension Inventory Version 3.0 (SC-HI v3.0) in Iranian population - Naddafi, Fatemehzahra; Jafari, Alireza; Hosseinzadeh Younesi, Elyas; Sajjadi, Moosa (Frontiers in Public Health, 2025)
IntroductionSelf-care is a key element of hypertension control. This study was carried out with the purpose of translating and investigating the psychometric features of the Persian version of Self-care of Hypertension Inventory Version 3.0 (SC-HI v3.0) in Iranian hypertensive population.MethodsThis cross-sectional study was carried out in 593 people with hypertension in 2023 in Gonabad city (Iran). The participants were included by stratified random sampling from the community health centers of Gonabad city. The translation of the scale was done according to the multi-stage guideline of the instrument developers. The validity of the SC-HI v3.0 was examined by qualitative face validity, qualitative and quantitative content validity and construct validity assessed by confirmatory factor analysis (CFA). The reliability of the SC-HI v3.0 was also evaluated by calculating intraclass correlation coefficient (ICC) and Cronbach’s alpha coefficient. Data analysis was done using Amos software version 24 and SPSS software version 25.ResultsIn the translation process, face validity, and content validity evaluation, almost all the items of SC-HI v3.0 were partially revised without changing the main concept. In the construct validity evaluation, the results of CFA confirmed the Persian version of SC-HI v3.0 with 21 items and including three scales of maintenance with two factors (7 items), monitoring with one factor (7 items), and management with one factor (7 items). Finally, in reliability evaluation, Cronbach’s alpha coefficient and ICC were 0.879 and 0.842, respectively.ConclusionConsidering the lack of a comprehensive and brief tool for measuring hypertension self-care in Iran, the Persian version of the SC-HI v3.0 with 21 items and 3 scales, can be a valid and reliable inventory for self-care evaluation in Iranian hypertensive patients.